2011
DOI: 10.1002/cbf.1781
|View full text |Cite
|
Sign up to set email alerts
|

The effects of periodized concurrent and aerobic training on oxidative stress parameters, endothelial function and immune response in sedentary male individuals of middle age

Abstract: The vascular endothelium plays a key role in arterial wall homeostasis by preventing atherosclerotic plaque formation. A primary causal factor of endothelial dysfunction is the reactive oxygen species. Aerobic exercise is ascribed as an important adjuvant therapy in endothelium-dependent cardiovascular disease. However, little is known about the effects of concurrent (aerobic + strength) training on that. For a comparison of the effects of aerobic and concurrent physical training on endothelial function, oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 54 publications
(87 reference statements)
2
28
0
Order By: Relevance
“…Lastly, inclusion of resistance training may have attenuated expected FMD improvements because resistance training may increase vascular stiffness and in combination with aerobic training may produce a null effect. 31 Consistent with this, pulse wave velocity did not improve among exercisers during our intervention (922 vs. 930 cm/s, p =0.87). 26 Two of the previously mentioned studies reporting improved FMD with combined aerobic and resistance training using either a circuit-training protocol that alternated 45-second aerobic and resistance exercises 22 or aerobic followed by resistance training.…”
Section: Discussionsupporting
confidence: 81%
“…Lastly, inclusion of resistance training may have attenuated expected FMD improvements because resistance training may increase vascular stiffness and in combination with aerobic training may produce a null effect. 31 Consistent with this, pulse wave velocity did not improve among exercisers during our intervention (922 vs. 930 cm/s, p =0.87). 26 Two of the previously mentioned studies reporting improved FMD with combined aerobic and resistance training using either a circuit-training protocol that alternated 45-second aerobic and resistance exercises 22 or aerobic followed by resistance training.…”
Section: Discussionsupporting
confidence: 81%
“…7). Other laboratories have reported improvements in brachial artery FMD in response to aerobic exercise training in middleaged healthy and/or mildly hypertensive men (62,85). The results of studies performed in rodent models assessing EDD, generally in the carotid arteries and skeletal muscle arterioles, support these observations in human subjects (17,70,71).…”
Section: Functional Effectsmentioning
confidence: 58%
“…However, an intervention trial in which healthy men and women underwent swim training found a significant improvement in brachial artery FMD (57). In men, both walk/jog/run-and cycling-based aerobic exercise programs have been associated with enhanced endothelial function in MA/O subjects (12,59,62), although lack of improvements also has been reported with cycle training (77). The intervention studies in women showing improvements in brachial artery FMD with aerobic exercise have utilized walking and/or cycling training (2,72,86).…”
Section: Functional Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of cells producing ROS suggests that not all monocytes were equally phagocytically active, and our results may be influenced by the training-induced increase in CD16-negative monocytes (see below) which could influence ROS production. Schaun and colleagues observed no difference in monocyte phagocytosis following 12 weeks of aerobic exercise training [35], though they used a TLR2 agonist (zymosan) rather than bacteria. Of interest is that basal and stimulated monocyte ROS production and phagocytosis is suggested to be higher in obese individuals [36].…”
Section: Discussionmentioning
confidence: 99%